1999
DOI: 10.1115/1.2893951
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Dynamic Behavior of a Flexible Rotor With Auxiliary Support from a Clearance Bearing

Abstract: This paper investigates the steady-state responses of a rotor system supported by auxiliary bearings in which there is a clearance between the rotor and the inner race of the bearing. A simulation model based upon the rotor of a production jet engine is developed and its steady-state behavior is explored over a wide range of operating conditions for various parametric configurations. Specifically, the influence of rotor imbalance, clearance, support stiffness and damping is studied. Bifurcation diagrams are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…A four-bar mechanism was implemented as an example and Lagrangian approach was used to model the motion of a rocker arm pin at the ground connection. The effect of joint clearance in planar problems without treating the effect of lubrication was discussed by Xie et al [14]. Bifurcation diagrams were used as a tool to investigate the dynamic behavior of system.…”
Section: Introductionmentioning
confidence: 99%
“…A four-bar mechanism was implemented as an example and Lagrangian approach was used to model the motion of a rocker arm pin at the ground connection. The effect of joint clearance in planar problems without treating the effect of lubrication was discussed by Xie et al [14]. Bifurcation diagrams were used as a tool to investigate the dynamic behavior of system.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic rotor-to-stator model was also widely used in rotor-auxiliary bearing interaction system. Large numbers of researches were made by Xie et al [38] , Cole [39] , Keogh and Cole [40] , and Sahinkaya et al [41] in this field.…”
Section: Introductionmentioning
confidence: 97%
“…Mingori, et al have shown the stability of spin rocket under the internal mass motion and axial thrust [4] . Xie, et al have analyzed the dynamic behavior of a flexible jet rotor with the auxiliary support from a clearance bearing [5] .…”
Section: Introductionmentioning
confidence: 99%